2010
DOI: 10.3109/02699200903437914
|View full text |Cite
|
Sign up to set email alerts
|

Development of voice onset time in standard-Greek and Cypriot-Greek-speaking preschoolers

Abstract: The current investigation examined the development of voice onset time (VOT) in Standard-Greek (SG) and Cypriot-Greek (CG)-speaking children at age levels 2;0-2;5, 2;6-2;11, 3;0-3;5, and 3;6-4;0 years. SG presents with a two-way voicing contrast (voiced and voiceless unaspirated stops) whereas CG is a three-way contrast dialect containing voiceless unaspirated, voiceless aspirated, and pre-voiced stops. A cross-sectional design was used. The main goals were: (1) to determine the age at which Greek and Cypriot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…Conversely, Greek word-initial voiced stops almost always have lead VOT values as in Spanish or French (Botinis, Fourakis & Prinou, 2000; Arvaniti, 2007). However, Okalidou, Petinou, Theodorou, & Karasimou (2010) found that 2-year-old Standard Greek-speaking children could produce adult-like lead VOT. Perhaps, in these two languages, the age of mastery of voiced stops cannot be predicted by VOT alone.…”
Section: 0 Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Conversely, Greek word-initial voiced stops almost always have lead VOT values as in Spanish or French (Botinis, Fourakis & Prinou, 2000; Arvaniti, 2007). However, Okalidou, Petinou, Theodorou, & Karasimou (2010) found that 2-year-old Standard Greek-speaking children could produce adult-like lead VOT. Perhaps, in these two languages, the age of mastery of voiced stops cannot be predicted by VOT alone.…”
Section: 0 Introductionmentioning
confidence: 90%
“…Greek-speaking children master voiced stops at very young ages (Okalidou et al, 2010; Kollia, 1987; Beckman & Edwards 2010). We speculate that this early mastery pattern of voiced stops in Greek might be due to their amplitude characteristics, which cannot be captured by VOT.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Several studies of other languages show the same tendency with higher standard deviations in children when compared to adults (Koenig, 2001;Okalidou, Petinou, Theodorou and Karasimou, 2010).…”
Section: Discussionmentioning
confidence: 54%
“…In particular, it would be of interest to examine the acquisition of voiced stops in the Cretan dialect. Several studies (Kong et al, 2007;Okalidou et al, 2010) have shown relatively early acquisition of voiced stops in dialects of Greek with prenasalization of voiced stops. Kong et al (2007) found that many productions of so-called "voiced" stops by children were, in fact, fully nasalized.…”
Section: Discussionmentioning
confidence: 99%